What changes in maxillary morphology from distraction osteogenesis maxillary expansion (DOME) correlate with subjective and objective OSA measures? - Yoon, Audrey; Kim, Tae Keong; Abdelwahab, Mohamed; Nguyen, Mai; Suh, Hee Yeon; Park, Joorok; Oh, Heesoo; Pirelli, Paola; Liu, Stanley Yung-Chuan (Sleep & breathing, 2023)
Objectives To correlate skeletal and airway measures on imaging with polysomnographic and self-reported measures after distraction osteogenesis maxillary expansion (DOME), in the effort to identify clinically relevant sites of expansion to guide treatment for adult patients with obstructive sleep apnea (OSA). Materials and methods This is a retrospective study reviewing subjects who underwent DOME and had the complete set of the following data: peri-treatment cone-beam computed tomography (CBCT) scans, polysomnography (PSG), Epworth Sleepiness Scale (ESS), and nasal obstruction symptom (NOSE) scores. Results Of 132 subjects who underwent DOME, 35 met inclusion criteria (71% men, mean age 27.7 ± 6.5 years, mean BMI 26.0 ± 6.4 kg/m 2 ) and were enrolled in the study. There was a significant reduction in the NOSE score from 11.4 ± 5.5 to 3.6 ± 3.1, in the ESS score from 12.0 ± 4.6 to 7.1 ± 4.7, and in the apnea–hypopnea index (AHI) from 17.1 ± 15.8 to 7.01 ± 6.2 ( p < 0.0001), after DOME. Nasal floor width at the nasopalatine canal level showed a statistically significant correlation with AHI reduction ( p < .0001). Conclusions DOME is significantly associated with reduction of nasal obstruction, sleepiness, and severity of OSA. The findings suggest that expansion at the anterior third of the bony nasal passage, specifically where the nasopalatine canal is located predicts its clinical efficacy. This site may be a useful target anatomically via imaging.